The Influence Of Knowledge Management Effectiveness On Administrative Innovation Among Malaysian Manufacturing Firms - Tan , Cheng Ling; Mohd. Nasurdin, Aizzat (Asian Academy of Management (AAM), 2010)
The purpose this study is to examine the direct effect of knowledge management effectiveness on administrative innovation. Knowledge management effectiveness is conceptualised as comprising of knowledge acquisition effectiveness, knowledge sharing effectiveness, and knowledge application effectiveness. Three hypothesised relationships were tested using a sample of 171 large manufacturing firms in Malaysia. The results derived from the regression analyses showed that of the three dimensions of knowledge management effectiveness (knowledge acquisition effectiveness, knowledge sharing effectiveness, and knowledge application effectiveness), only knowledge acquisition effectiveness was found to have a significant positive effect on administrative innovation. The implications of the study as well as suggestions for future studies are also discussed.